M3S Squad: Considering Cyborgs for Future Sexual Health Prevention Programs - Zofia Sleziak (Body, Space & Technology Journal, 2007)
Amidst fiscal constraint and burgeoning health care demands, an innovative response to sexually transmitted infections was piloted in Quebec (Canada). This response arose out of the relationship of man and machine and resulted in the creation of cyborgs as a communication medium for the dissemination of safer sex messaging. These cyborgs physically carried the prevention message to a traditionally ‘at-risk’ audience, engaged their attention, and elicited an observable response. This paper proposes that at least a small portion of the resources allocated to re-creating old technologies may be diverted to researching and developing original and highly artistic prevention campaigns in Public Health.